Evaluasi Radiologi pada Kasus Fraktur Basis Kranii - Angelika, Irene; Prasetyo, Eko (Jurnal Biomedik : JBM, 2021)
Abstract: Skull base fractures, namely fractures that extend through the base of the anterior, middle, or posterior cranial fossa that occur in about 7% to 16% of non-perforating head injuries, are caused by trauma with relatively high velocity, and are most frequently caused by a high-speed motor vehicle accident. Pedestrian injuries, falls and assault are other related causes. Penetrating trauma, especially gunshot wounds, is much rarer and accounts for less than 10% of cases. This research method is in the form of literature review. The literature was collected using several databases, such as ClinicalKey and Google Scholar with the keywords radiology and base skull fracture, this article was obtained according to keywords and was screened according to inclusion and exclusion criteria. There are 11 journals full text that will be reviewed according to the criteria consisting of one retrospective study, one clinical review, two literature reviews, three review articles, one prospective study, one case report, one descriptive study and one comparative study. This study shows that 11 literature reviews radiological evaluation in the case of cranii basis. In conclusion, radiology is the most important examination required in patients who are suspected of suffering from fracture of the base cranii is a non-contrast head CT scan.. Other radiological examinations that can be used are plain radiographs of the head, and angiography.Key words: Skull base fractures, basis cranii, radiology  Abstrak: Fraktur basis cranii, yaitu fraktur yang meluas melalui dasar fossa kranial anterior, tengah, atau posterior yang terjadi pada sekitar 7% hingga 16% dari cedera kepala non-perforans, disebabkan oleh trauma dengan kecepatan yang relatif tinggi, dan paling sering disebabkan oleh kecelakaan kendaraan bermotor berkecepatan tinggi. Cedera pejalan kaki, jatuh, dan penyerangan adalah penyebab terkait lainnya. Trauma tembus, terutama luka tembak jauh lebih jarang dan terhitung kurang dari 10% kasus. Metode penelitian ini dalam bentuk studi pustaka (lirerature review). Literature di kumpulkan menggunakan beberapa database, seperti ClinicalKey dan Google Scholar dengan kata kunci radiology dan base skull fracture, artikel ini didapatkan sesuai dengan kata kunci dan dilakukan skrining sesuai kriteria inklusi dan eksklusi. Terdapat 11 jurnal full text yang akan dilakukan review yang sesuai kriteria terdiri atas satu retrospective study, satu clinical review, dua literature review, tiga review article, satu prospective study, satu case report, satu descriptive study dan satu comparative study. Penelitian ini menunjukkan bahwa 11 literatur mengulas tentang evaluasi radiologi pada kasus basis cranii. Sebagai simpulan, radiologis merupakan pemeriksaan paling utama yang diperlukan pada pasien yang dicurigai menderita fraktur basis cranii adalah pemeriksaan CT-Scan non kontras kepala.. Pemeriksaan radiologi lain yang dapat digunakan adalah pemeriksaan foto polos kepala, dan angiografi.Kata kunci: Patah tulang dasar kepala, basis kranii, radiologi